Transmission of Drug-Resistant HIV-1 Variants Among Individuals with Recent Infection in Southern Poland - Smolen-Dzirba, Joanna; Rosinska, Magdalena; Kruszynski, Piotr; Bratosiewicz-Wasik, Jolanta; Janiec, Janusz; Beniowski, Marek; Bociaga-Jasik, Monika; Jablonowska, Elzbieta; Szetela, Bartosz; J. Wasik, Tomasz (Current HIV Research, 2013)
Transmitted drug resistance (TDR) is an important public health issue, because it may affect the outcome of antiretroviral treatment. The prevalence of human immunodeficiency virus type 1 (HIV-1) with TDR mutations defined according to the list of the World Health Organization was investigated among 53 therapy-naive persons with confirmed recent HIV-1 infection diagnosed in Poland, in the years 2008-2010. Proviral DNA was amplified, sequenced, and screened for the TDR mutations in the pol gene fragments coding for the whole protease and the initial 256 residues of the reverse transcriptase. The frequency of sequences with at least one TDR mutation was 11.3%. In four (7.5%) sequences at least one resistance mutation related to reverse transcriptase inhibitors was identified, and in further two (3.8%) sequences one mutation related to protease inhibitors' resistance was present. The moderate rate of TDR highlights the need for a continuous surveillance and resistance testing among treatment-naive individuals to optimize treatment effects within a country.
Keywords: pol gene